A Randomized Double-Blind Placebo-Controlled Pilot Trial on the Effects of Testosterone Undecanoate Plus Dutasteride or Placebo on Muscle Strength, Body Composition, and Metabolic Profile in Transmen. Issue 3 (30th January 2021) - Gava, Giulia; Armillotta, Francesca; Pillastrini, Paolo; Giagio, Silvia; Alvisi, Stefania; Mancini, Ilaria; Morselli, Paolo Giovanni; Seracchioli, Renato; Meriggiola, Maria Cristina
ABSTRACT: Background: While the effects of androgens on muscle are well described in hypogonadal men, literature is still scarce on muscular strength or size variations in transmen; in this population there are no data regarding the relative effect of testosterone (T) and its metabolite dihydrotestosterone on muscle. Aim: Our primary objective was to compare the effects on muscle strength of 54-week administration of testosterone undecanoate (TU) combined with the 5α-reductase inhibitor dutasteride (DT) or placebo (PL). Secondary outcomes included evaluation of body composition, bone, cutaneous androgenic effects, and metabolic variations. Methods: In this randomized, double-blind PL-controlled pilot trial, 16 ovariectomized transmen were randomized to receive TU 1, 000 mg IM at week 0, 6, 18, 30, 42 plus a PL pill orally daily (TU + PL, n = 7) or plus DT 5 mg/d (TU + DT, n = 7). Outcomes: At week 0 and 54 the following parameters were evaluated: isokinetic knee extension and flexion peak torque and handgrip strength, body composition, and bone mineral density, biochemical, hematological, and hormonal parameters. RESULTS: Handgrip and lower limb strength increased significantly in both groups with no differences between the 2 groups. Fat mass decreased and lean mass increased significantly similarly in both groups. Metabolic parameters remained stable in the 2 groups except for high-density lipoprotein cholesterol that was reduced in both groups. Hepatic and renal function remained normal in both groups and no major adverse effects were registered in either group. Clinical Implications: These results may be particularly relevant for transmen experiencing cutaneous androgenic adverse events such as acne and androgenetic alopecia and in light of the development of non-5α-reduced androgens. Strengths & Limitations: The strength of this study was the randomized, double-blind PL-controlled design, while the small number of subjects was definitely the biggest limitation. CONCLUSION: For the first time we demonstrated that the addition of DT does not impair the anabolic effects of T on muscles in transmen previously exposed to T, supporting the hypothesis that the conversion in dihydrotestosterone is not essential for this role.